EMOTIONAL INTELLIGENCE AND STUDENTS’ TRANSLATION ABILITY AT ENGLISH DEPARTMENT OF HALU OLEO UNIVERSITY - Badarun, Nurfadillah; Rohmana, Rohmana; Alberth, Alberth (Journal of Teaching of English, 2020)
Emotional intelligence and translation ability level vary among individual students. The present study seeks to examine (1) the relationship between students’ emotional intelligence and their translation ability. It also aims at (2) determining which dimension of emotional intelligence can best predict students’ translation ability. The study employed a descriptive quantitative design. Participants of this study were the sixth semester students in Translation Class at English Education Department of Halu Oleo University. The population was 101 students and 80 students were taken as the sample using purposive sampling technique. The data were obtained from emotional intelligence questionnaire and students’ translation scores. The analysis used Pearson correlation and Regression analysis by using SPSS 20. The results reveal that (1) there is no significant relationship between emotional intelligence and students’ translation ability, and (2) one of the dimensions of emotional intelligence have statically relationship with students’ translation score that is self-regulation dimension. Keywords: Relationship; Emotional Intelligence; Translation Ability